Improved Chemical and Radiochemical Synthesis of Neuropeptide Y Y2 Receptor Antagonist N-Methyl-JNJ-31020028 and Preclinical Positron Emission Tomography Studies - Inês C. F. Fonseca; Mariana Lapo Pais; Fábio M. S. Rodrigues; José Sereno; Miguel Castelo-Branco; Cláudia Cavadas; Mariette M. Pereira; Antero J. Abrunhosa (MDPI AG, 2024)
Neuropeptide Y (NPY) is one of the most abundant peptides in the central nervous system of mammals and is involved in several physiological processes through NPY Y1, Y2, Y4 and Y5 receptors. Of those, the Y2 receptor has particular relevance for its autoreceptor role in inhibiting the release of NPY and other neurotransmitters and for its involvement in relevant mechanisms such as feeding behaviour, cognitive processes, emotion regulation, circadian rhythms and disorders such as epilepsy and cancer. PET imaging of the Y2 receptor can provide a valuable platform to understand this receptor's functional role and evaluate its potential as a therapeutic target. In this work, we set out to refine the chemical and radiochemical synthesis of the Y2 receptor antagonist N-[11C]Me-JNJ31020028 for in vivo PET imaging studies. The non-radioactive reference compound, N-Me-JNJ-31020028, was synthesised through batch synthesis and continuous flow methodology, with 43% and 92% yields, respectively. N-[11C]Me-JNJ-31020028 was obtained with a radiochemical purity > 99%, RCY of 31% and molar activity of 156 GBq/μmol. PET imaging clearly showed the tracer's biodistribution in several areas of the mouse brain and gut where Y2 receptors are known to be expressed.